Optimization Control of Flexible Power Supply System Applied to Offshore Wind–Solar Coupled Hydrogen Production - Lishan Ma; Rui Dong; Qiang Fu; Chunjie Wang; Xingmin Li (Journal of Marine Science and Engineering, 2025)
The inherent randomness and intermittency of offshore renewable energy sources, such as wind and solar power, pose significant challenges to the stable and secure operation of the power grid. These fluctuations directly affect the performance of grid-connected systems, particularly in terms of harmonic distortion and load response. This paper addresses these challenges by proposing a novel harmonic control strategy and load response optimization approach. An integrated three-winding transformer filter is designed to mitigate high-frequency harmonics, and a control strategy based on converter-side current feedback is implemented to enhance system stability. Furthermore, a hybrid PI-VPI control scheme, combined with feedback filtering, is employed to improve the system’s transient recovery capability under fluctuating load and generation conditions. Experimental results demonstrate that the proposed control algorithm, based on a transformer-oriented model, effectively suppresses low-order harmonic currents. In addition, the system exhibits strong anti-interference performance during sudden voltage and power variations, providing a reliable foundation for the modulation and optimization of offshore wind–solar coupled hydrogen production power supply systems.

Experimental and Numerical Investigation on Mechanical Properties of Large-Diameter Metallurgically Clad Pipes - Feng Wang; Yanan Gao; Zhiguo Hu; Shuo Yang; Zhenying Cui; Rui Fu; Lin Yuan (Journal of Marine Science and Engineering, 2025)
Bimetallic-clad pipes demonstrate exceptional advantages in transporting corrosive oil and gas through the combination of the load-carrying capacity of the base material and the anti-corrosive function of the thin layer of corrosion-resistant alloy. This study investigates the mechanical properties of 24-inch X65 + Alloy625 metallurgically clad pipes through experimental tests and finite element analysis. Uniaxial tensile testing with digital image correlation reveals uniform deformation between the base and clad layers until interfacial failure initiates at an average strain threshold of 34.17%. Microstructural characterization shows continuous metallurgical bonding, with the X65 layer exhibiting polygonal ferrite and bainitic phases, contrasting with the austenitic equiaxed grain structure of Alloy625. In terms of numerical modeling, finite element analyses that consider both initial geometric imperfections and manufacturing-induced residual stresses are performed to evaluate the bending response of the clad pipe. The effect of initial ovality and residual stresses on its bending capacity is also studied.

Effect of Licorice on Gene Expression Related to the Growth of Asian Seabass Lates calcarifer - Rui Yang; Wang Zhao; Yifu Wang; Zhengyi Fu; Jing Hu; Shengjie Zhou; Minghao Li; Zhenhua Ma (Journal of Marine Science and Engineering, 2024)
The Asian seabass (Lates calcarifer) has high economic value and is the primary aquaculture species in China. Licorice (Glycyrrhiza uralensis) as a feed additive has demonstrated significant immunological benefits in aquaculture. However, its effects on the growth of aquatic animals are largely unexplored. This study explored the influence of licorice on the level of growth-related genes in Asian seabass by conducting an experiment using artificial feed with 0%, 1%, 3%, and 5% licorice. The impact on growth performance and the expression of several genes, including growth hormone–releasing hormone (GHRH), growth hormone (GH), growth hormone receptor (GHR), insulin-like growth factor 1 (IGF1), IGF2, IGF2 receptor (IGF2R), myostatin 1 (MSTN1), and myostatin 2 (MSTN2), were studied over 56 d. According to the results, the 3% and 5% licorice-supplemented diets significantly improved survival rates and weight gain compared to the control group. Licorice affected the level of growth-associated genes in Asian seabass and significantly increased the levels of GHR and IGF1 in the liver. However, a 5% licorice diet downregulated the expression of IGF2. As the licorice content in the diet increased, the levels of IGF2R and MSTN1 in the muscle tissue first decreased and then increased, and licorice addition inhibited the MSTN2 expression. The inclusion of licorice in the feed led to a significant downregulation of the GH and GHRH expression (p

Antioxidant and Metabolic Response to Acute Acidification Stress of Juvenile Yellowfin Tuna (Thunnus albacares) - Xiaoyan Wang; Rui Yang; Zhengyi Fu; Lei Zhao; Zhenhua Ma (Journal of Marine Science and Engineering, 2024)
This study aimed to explore the impact of acute acidification on the antioxidant, metabolic performance, and liver histology of juvenile yellowfin tuna. The experiment subjected juvenile yellowfin tuna to a pH gradient environment of 8.1, 7.6, 7.1, and 6.6 for 48 h. The findings indicate that a seawater pH of 7.1 significantly impacts the antioxidant and metabolic systems of the juvenile yellowfin tuna in comparison to the control group. At pH 7.1, there were observed increases in glutathione reductase (GR), total antioxidant capacity (T-AOC), lactate dehydrogenase (LDH), hexokinase (HK), pyruvate kinase (PK), sodium-potassium ATPase (Na+K+-ATP), and calcium-magnesium ATPase (Ca2+Mg2+-ATP). Conversely, low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides (TGs) were not significantly different across the treatment groups. However, an increase in transaminases at pH 7.1 suggested potential liver damage, which was further supported by observed structural liver tissue degeneration and hepatocyte vacuolation. In conclusion, under conditions of acute acidification stress, there is a decrease in antioxidant capacity and a suppression of metabolic levels in juvenile yellowfin tuna, leading to oxidative damage. This study lays the foundation for an in-depth understanding of the response mechanisms of juvenile yellowfin tuna in response to seawater acidification as well as healthy tuna farming in the broader context of seawater acidification.

The Photoperiod Significantly Influences the Growth Rate, Digestive Efficiency, Immune Response, and Antioxidant Activities in the Juvenile Scalloped Spiny Lobster (Panulirus homarus) - Yinggang Wang; Rui Yang; Zhengyi Fu; Zhenhua Ma; Zemin Bai (Journal of Marine Science and Engineering, 2024)
This study aimed to elucidate the effects of different photoperiods (0 L:24 D, 6 L:18 D, 12 L:12 D, 18 L:6 D, 24 L:0 D, “Light (L) and Dark (D)”) on the growth performance and physiological responses of the juvenile scalloped spiny lobster (Panulirus homarus). Over a period of 56 days, parameters such as growth rate, digestive enzyme, immune enzyme, and antioxidant enzyme were meticulously evaluated in 90 lobsters subjected to these varying light conditions. The present study found no significant differences in survival rate (SR), molting frequency (MF), and meat yield production (MYP) among the various photoperiod treatments (p > 0.05). Notably, the highest weight gain rate (WGR) and specific growth rate (SGR) were observed under a 12 L:12 D photoperiod. In the continuous dark phase (0 L:24 D), pepsin (PEP) activity remained high in gastric tissues, while trypsin (TRYP) and chymotrypsin (CHT) activities reached the highest in hepatopancreas tissues. The α-amylase (AMS) activity in the hepatopancreas was most elevated under 18 L:6 D, and the optimal lipase (LPS) activity was recorded under 12 L:12 D. The activity of acid phosphatase (ACP) in the hepatopancreas was highest in the absence of light (0 L:24 D), whereas the activities of alkaline phosphatase (AKP) and lysozyme (LZM) were most effective under the 12 L:12 D photoperiod. The total antioxidant capacity (T-AOC), along with catalase (CAT) and superoxide dismutase (SOD) activities of the hepatopancreas reached the highest at 12 L:12 D. The highest activity of glutathione peroxidase (GSH-Px) was seen under 18 L:6 D. The concentration of malondialdehyde (MDA), a marker of oxidative stress, was found to be highest under 12 L:12 D. Consequently, this specific photoperiod is essential for achieving optimal growth and maintaining appropriate physiological balance in the scalloped spiny lobster during aquaculture. These findings provide a foundational guideline for establishing the lighting environment in the farming of the juvenile scalloped spiny lobster.

Distribution Characteristics and Factors Controlling Different Phosphorus Fractions in the Soils and Sediments of an Inland Lagoon - Kun Yuan; Rui Wang; Bo He; Guowei Fu; Yanwei Song; Lixin Pei; Shichao Fan; Fangyi Gao (Journal of Marine Science and Engineering, 2024)
Lagoons, significant coastal wetlands, stand out for their vital role in the cycles and transformations of phosphorus. However, the relationship between the spatial distributions of various phosphorus forms in the soil and sediments of lagoon areas remains unclear. This study investigated the phosphorus fractions and distribution patterns in the soil and sediments from Shimei Inland Sea, Hainan Province, China, and identified the factors controlling phosphorus distribution and its relationship with lagoon eutrophication. The results revealed significant enrichment of inorganic phosphorus (IP) in the Shimei Inland Sea (64.1–679.0 mg/kg) and offshore areas (56–627.2 mg/kg), while organic phosphorus (OP) was relatively concentrated in land (60–744.3 mg/kg), suggesting that the productivity of the terrestrial ecosystem controlled the OP content and IP formed from the mineralization of OP was more likely to leach into the water and combine with minerals. Total phosphorus (TP) content was negatively affected by pH, and organic matter, cation exchange capacity and iron/aluminum oxides showed significant positive correlations with TP content. These findings highlighted the coupled impact of soil and sediment physicochemical properties on phosphorus enrichment and transformation, providing theoretical support for the ecological restoration of ecosystems in tropical coastal wetlands.

Distribution Analysis of Local Ice Pressures in the Indentation Test at Various Velocities - Guojun Wang; Qianjin Yue; Dayong Zhang; Yanghua Fu; Xin Peng; Rui Dong (Journal of Marine Science and Engineering, 2022)
When sea ice acts on vertical structures, there are much higher pressures in localized areas known as high-pressure zones (HPZs) than in other areas. The damage failure mode of sea ice varies with the sea ice velocity and affects the distribution of HPZs. In this study, an indentation test that drives ice sheet interaction with a vertical rigid plate (indentor) was designed, and a pressure sensor (consisting of 32 × 32 small pressure units of 100 mm2) was installed on the indentor face to measure the local ice pressure (LIP) at various velocities. The distribution of the LIPs along the ice thickness, the probability distribution of the LIPs and the distribution relationship of the LIPS in space and time were obtained from the measurement. The results show that the LIPs were mainly distributed in the middle of the sea ice, which is consistent with full-scale observations and previous research. Ductile failure of the sea ice results in a larger LIP distribution area than brittle failure at the same threshold kt (kt = σL/σcr). The probability distribution of the LIPs decreases exponentially with increasing pressure and follows a lognormal distribution. The maximum LIP appears at the peak moment of the global force when the sea ice failure mode is mainly ductile failure. However, the maximum LIP may not occur at the peak moment when the sea ice failure is mainly brittle failure and, instead can appear at any moment in the global force time history curve. The HPZ (which is larger than 7/8 times the maximum LIP) area is less than 2% of the nominal contact area at various velocities. The influence of the sea ice velocity on the spatial and temporal distribution of LIP is analyzed, and the results provide a reference for designing structures with local strength in ice regions.